2014
DOI: 10.1080/00140139.2014.934301
|View full text |Cite
|
Sign up to set email alerts
|

The influence of rice plow handle design and whole-body posture on grip force and upper-extremity muscle activation

Abstract: The findings of this work may be used to educate farmers on the potential for hand and arm injury in rice cultivation activities. Results may also provide a basis for redesign of existing tiller handles to promote neutral wrist posture, greater efficiency in muscle use and machine control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…For the flexor muscles, the decrease in wrist joint angles toward palmar flexion induced a reduction in torque output. This suggests that in the case of rot-HP utilization, a surgeon might need less muscular effort to conduct laparoscopic procedures than with the fixed-HP in the area of Quadrants B and C. This hypothesis is supported by the findings of the present study with a reduction flexor muscle activity in Quadrant C at the lower working height as well as the findings of Swangnetr and colleagues (2014), who found increased muscle efficiency (more grip force per muscle activity) using an improved rice plow handle design that induced more neutral wrist positions.…”
Section: Discussionsupporting
confidence: 85%
“…For the flexor muscles, the decrease in wrist joint angles toward palmar flexion induced a reduction in torque output. This suggests that in the case of rot-HP utilization, a surgeon might need less muscular effort to conduct laparoscopic procedures than with the fixed-HP in the area of Quadrants B and C. This hypothesis is supported by the findings of the present study with a reduction flexor muscle activity in Quadrant C at the lower working height as well as the findings of Swangnetr and colleagues (2014), who found increased muscle efficiency (more grip force per muscle activity) using an improved rice plow handle design that induced more neutral wrist positions.…”
Section: Discussionsupporting
confidence: 85%
“…A new tool for planting rice was also carried out, thus avoiding doing this activity manually [44]. Other improvements in this type of crop were the modification of the equipment handles used for the plow, [45] and the mechanization of the tasks of transplantation and start-up in rice cultivation [46].…”
Section: Musculoskeletal Disorders In Agriculturementioning
confidence: 99%
“…These studies include the study by Swangnetr et al. [32] and others that studied ergonomic-related risk identification and pain analysis for farm workers involved in rice field preparation; Chanprasit and Kaewthummanukul [33] studied corn plantation farm workers and found that most of their working postures did not adhere to ergonomic recommendations such as the prevalence of body bending (9.2%), prolonged standing (97.7%), and manual heavy lifting (90%) [33] . In addition to those described above, studies were also conducted for sugarcane, rice, and rubber tree plantation workers [15] , [16] .…”
Section: Introductionmentioning
confidence: 99%